4. Complete the following. a) Simplify: i) \( \left(a-\frac{1}{a}\right)\left(a^{2}+1+\frac{1}{a^{2}}\right) \) ii) \( \left(a-\frac{1}{a}\right)^{2} \). b) Calculate the value of: i) \( a^{2}+\frac{1}{a^{2}} \), if \( a-\frac{1}{a}=3 \) ii) \( a^{3}-\frac{1}{a^{3}} \).
Real Tutor Solution
Answer
Solution
Reviewed and approved by the UpStudy tutoring team
Extra Insights
To simplify and solve the given expressions, let’s break them down. a) i) To simplify \( \left(a-\frac{1}{a}\right)\left(a^{2}+1+\frac{1}{a^{2}}\right) \), we can expand it as follows: \[ = a(a^2 + 1 + \frac{1}{a^2}) - \frac{1}{a}(a^2 + 1 + \frac{1}{a^2}) \] \[ = a^3 + a - \frac{1}{a}(a^2 + 1) - 1 \] Combining terms gives us: \[ = a^3 + a - a - \frac{1}{a} - 1 \\ = a^3 - \frac{1}{a} - 1. \] ii) For \( \left(a-\frac{1}{a}\right)^{2} \): \[ = a^2 - 2 \cdot a \cdot \frac{1}{a} + \left(\frac{1}{a}\right)^{2} \\ = a^2 - 2 + \frac{1}{a^2} \\ = a^2 + \frac{1}{a^2} - 2. \] b) i) To calculate \( a^{2}+\frac{1}{a^{2}} \) given \( a-\frac{1}{a}=3 \), we know: \[ \left(a - \frac{1}{a}\right)^{2} = a^{2} - 2 + \frac{1}{a^{2}}. \] Thus, \[ 3^{2} = a^2 - 2 + \frac{1}{a^2} \implies 9 = a^{2} + \frac{1}{a^{2}} - 2 \implies a^{2} + \frac{1}{a^{2}} = 11. \] ii) To find \( a^{3}-\frac{1}{a^{3}} \), we use the identity: \[ a^{3} - \frac{1}{a^{3}} = \left(a - \frac{1}{a}\right)(a^{2} + 1 + \frac{1}{a^{2}}). \] With \( a - \frac{1}{a} = 3 \) and \( a^{2} + \frac{1}{a^{2}} = 11 \), we can calculate: \[ = 3 \left( 11 + 1 \right) = 3 \cdot 12 = 36. \] Thus, the final answers are: a) i) \( a^3 - \frac{1}{a} - 1 \), ii) \( a^2 + \frac{1}{a^2} - 2 \); b) i) \( 11 \), ii) \( 36 \).